2010
DOI: 10.1111/j.1540-627x.2010.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CEO Gender on Market Orientation and Performance in Service Small and Medium-Sized Service Businesses

Abstract: This study examines the effects of CEO gender on market orientation and performance (growth and profitability) among a sample of small and medium-sized service businesses. Gender was found to have significant indirect effects (via market orientation) on both market performance (growth) and financial performance (profitability). That is, female-led service SMEs perform significantly better due to their stronger market orientation relative those led by males. The findings further suggest that female-led firms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
99
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 91 publications
(117 reference statements)
11
99
1
5
Order By: Relevance
“…Among the studies related to the CEO characteristics that determine the outcomes and competitiveness of SMEs, the following areas have been most frequently studied: background and capacity (e.g., Davis, Babakus, Englis, & Pett, 2010;Lee & Kim, 2003;Mazzi, 2011;Park, 2005;Park & Lee, 2011;Soriano & Castrogiovanni, 2012;Thong & Yap, 1995); leadership (e.g., Blackburn, Hart, & Wainwright, 2013;Chung & Park, 2010;Kim, 2007;Zhao, Seibert, & Lumpkin, 2010); and entrepreneurial spirit (e.g., Buyl, Boone, Hendriks, & Matthyssens, 2011;Daily & Dalton, 1992;Kim & Jung, 2015;Won, Hong, & Cha, 2015). In these studies, the CEO's characteristics were shown to affect organisational effectiveness, business performance, and export performance through innovative activities related to the learning ability of the organisation, organisational culture, and technological development.…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies related to the CEO characteristics that determine the outcomes and competitiveness of SMEs, the following areas have been most frequently studied: background and capacity (e.g., Davis, Babakus, Englis, & Pett, 2010;Lee & Kim, 2003;Mazzi, 2011;Park, 2005;Park & Lee, 2011;Soriano & Castrogiovanni, 2012;Thong & Yap, 1995); leadership (e.g., Blackburn, Hart, & Wainwright, 2013;Chung & Park, 2010;Kim, 2007;Zhao, Seibert, & Lumpkin, 2010); and entrepreneurial spirit (e.g., Buyl, Boone, Hendriks, & Matthyssens, 2011;Daily & Dalton, 1992;Kim & Jung, 2015;Won, Hong, & Cha, 2015). In these studies, the CEO's characteristics were shown to affect organisational effectiveness, business performance, and export performance through innovative activities related to the learning ability of the organisation, organisational culture, and technological development.…”
Section: Introductionmentioning
confidence: 99%
“…Gender plays an important role here. Women are able to apply ideas, skills and knowledge (Davis et al 2010) and place strong emphasis on communication skills (Connerley et al, 2008). Moreover, female CEOsalso rate self-reported performance higher than men (Sorenson et al, 2008).…”
Section: Performance Evaluationsmentioning
confidence: 99%
“…Transaction cost theory assumes that individuals who are aware of possible differences between them and others will be more willing to collaborate to achieve concrete and defined goals (Williamson, 1985) and networking is a basic form of collaboration that has positive effects on performance (cf: Hays et al, 2011;Davis et al, 2010;McMurry et al, 2012) but some collaborations may have negative effects on performance as well (Provan, Isett, & Milward, 2007). The observed gaps in the effect of collaborations on performance reflect the variations in performance measurement caused mainly by the diversity in stakeholders' expectations (Herman &Renz 2008) and lack of objective measures of performance.…”
Section: Performance Evaluationsmentioning
confidence: 99%
See 2 more Smart Citations